Impact Of Tax Amnesty Policy On Individual Taxpayer Compliance In Pontianak City - Fridensia Kamellia; Dedi Haryadi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study examines tax amnesty's impact on individual taxpayer adherence. Methodology: Data were gathered from 91 participants via an internet survey Likert-scale questionnaire and analyzed making use of validity, normality, and regression tests. Results: Findings show that tax amnesty significantly affects taxpayer compliance, with a regression result of 47.3%. Novelty: The study uniquely uses data from individual taxpayers in Pontianak collected through an online survey. Conclusion: The outcome confirm a favorable and noteworthy connection between tax amnesty and taxpayer compliance. Type of Paper: Empirical Research